Photovoltaic Materials and Devices Based on the Alloyed Kesterite Absorber (AgxCu1–x)2ZnSnSe4. Issue 10 (7th March 2016) - Gershon, Talia; Lee, Yun Seog; Antunez, Priscilla; Mankad, Ravin; Singh, Saurabh; Bishop, Doug; Gunawan, Oki; Hopstaken, Marinus; Haight, Richard
Abstract : The photovoltaic absorber Cu2 ZnSn(S x Se1– x )4 (CZTSSe) has attracted interest in recent years due to the earth‐abundance of its constituents and the realization of high performance (12.6% efficiency). The open‐circuit voltage in CZTSSe devices is believed to be limited by absorber band tailing caused by the exceptionally high density of Cu/Zn antisites. By replacing Cu in CZTSSe with Ag, whose covalent radius is ≈15% larger than that of Cu and Zn, the density of I–II antisite defects is predicted to drop. The fundamental properties of the mixed Ag‐Cu kesterite compound are reported as a function of the Ag/(Ag + Cu) ratio. The extent of band tailing is shown to decrease with increasing Ag. This is verified by comparing the optical band gap extrapolated from transmission data with the position of the room‐temperature photoluminescence peak; these values converge for the pure‐Ag compound. Additionally, the pinning of the Fermi level in CZTSSe, attributed to heavy defect compensation and band tailing, is not observed in the pure‐Ag compound, offering further evidence of improved electronic structure. Finally, a device efficiency of 10.2% is reported for a device containing 10% Ag (no antireflection coating); this compares to ≈9% (avg) efficiency for the baseline pure‐Cu CZTSe. Abstract : Band tailing in Cu2 ZnSn(S, Se)4 is demonstrated to be suppressed by replacing Cu with Ag, whose covalent radius is ≈15% larger. The optical band gap converges in energy with the position of the photoluminescence peak as the Ag content increases from 0% to 100%. This substitution also unpins the Fermi level from midgap and improves the photovoltaic conversion efficiency.